THE RELATIONSHIP OF CELEBRITY WORSHIP AND SELF CONTROL WITH SUBJECTIVE WELL BEING IN NCTZEN APPLICATION USERS X - Andriani, Berlyana; Nastiti, Dwi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the relationship between celebrity worship and self-control with subjective well-being among members of the NCTZen X community, a fan group dedicated to the K-Pop group NCT. Method: Employing a quantitative correlational approach, data were collected from 177 respondents in Sidoarjo using accidental sampling. Participants completed an online questionnaire comprising the Celebrity Attitude Scale (CAS), the Perceived Control Scale (PCS), and two subjective well-being instruments: the Satisfaction With Life Scale (SWLS) and the Scale of Positive and Negative Experience (SPANE). Results: The analysis revealed a significant relationship between celebrity worship and self-control with subjective well-being (R = 0.738; p < 0.05). Celebrity worship exhibited a negative correlation with subjective well-being (r = -0.563), while self-control demonstrated a positive correlation (r = 0.662). These findings indicate that excessive idolization is associated with reduced psychological well-being, whereas higher self-control correlates with improved well-being. Novelty: This study contributes to the limited literature by simultaneously examining the dual influence of celebrity worship and self-control on subjective well-being within a specific K-Pop fan community, highlighting the psychological dynamics of fandom engagement.